Method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate

By mixing industrial-grade lithium carbonate with organic acids, purifying with cation exchange resin, and reacting with hydrofluoric acid, the problem of difficulty in removing impurities in the prior art is solved, and the preparation of high-purity battery-grade lithium fluoride is achieved, which is suitable for industrial production.

CN119612555AInactive Publication Date: 2025-03-14HUBEI ZHONGYU NEW MATERIAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411738346.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, when using industrial-grade lithium carbonate to prepare battery-grade lithium fluoride, it is difficult to effectively remove impurities, affecting product quality.

Method used

By mixing industrial-grade lithium carbonate with organic acid, adjusting the pH value, purifying it with cation exchange resin, reacting with hydrofluoric acid, and after suction filtration and drying, a high-purity battery-grade lithium fluoride is finally obtained.

Benefits of technology

It has achieved efficient removal of impurities from industrial-grade lithium carbonate, the product purity reaches more than 99.95%, and the total yield reaches more than 99%, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium battery preparation, and particularly discloses a method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate, which comprises the following steps: (1) mixing industrial-grade lithium carbonate with organic acid until the solution does not react any more; (2) adding an auxiliary agent into the solution in the step (1), adjusting the pH value by using organic acid, and then filtering to obtain filtrate 1; (3) purifying the filtrate 1 obtained in the step (2) by using cation exchange resin, and filtering to obtain filtrate 2; (4) adding hydrofluoric acid into the filtrate 2 in the step (3), and stirring for reaction until no precipitate is generated, so as to obtain a mixture 3; (5) performing suction filtration on the mixture 3 in the step (4) to obtain filtrate and a filter cake; and cleaning and drying the obtained filter cake to obtain the battery-grade lithium fluoride. According to the preparation method provided by the invention, impurities in industrial-grade lithium carbonate can be effectively removed, the purity of the obtained battery-grade lithium fluoride product is high, and industrial production is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium battery preparation, and specifically relates to a method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate. Background Art

[0002] Lithium fluoride is the lithium salt of hydrofluoric acid. It is widely used in the fields of nuclear industry, enamel industry, optical glass manufacturing, preparation of lithium hexafluorophosphate, the raw material of lithium-ion battery electrolyte, etc. It is a very important lithium-based metal material. Usually, lithium fluoride is prepared by the following method: hydrofluoric acid is added to a suspension of lithium carbonate and water to directly react to obtain lithium fluoride. The main defect of this method is that the raw material of lithium carbonate is untreated, and its raw material impurity content directly determines the quality of the product. However, the national standard GB / T11075-2013 industrial-grade lithium carbonate contains a certain amount of impurity content: there are strict restrictions on the content of impurity elements such as sodium, potassium, calcium, magnesium, iron, aluminum, lead, copper, zinc, nickel, manganese, chlorine, and sulfate. For example, the mass fractions of sodium, iron, calcium, and SO42- should be ≤0.20%, 0.007%, 0.07%, 0.50%, etc., respectively, while the industry standard YS / T 661-2016 battery-grade lithium fluoride has more stringent requirements on the content of these impurity elements such as Na, K, Ca, Mg, Fe, SO42-, etc., usually requiring ≤0.001%-0.002%. If these impurities are not handled properly during the preparation of battery-grade lithium fluoride, it will directly affect the quality of the product.

[0003] Chinese patent document CN110817910A discloses a method for purifying industrial-grade lithium carbonate to prepare battery-grade lithium carbonate, wherein industrial-grade lithium carbonate is dissolved in formic acid solution, impurities are removed by cation exchange resin, and battery-grade lithium carbonate is prepared by ammonium carbonate reaction. The steps are relatively complicated, especially the step of adding ammonium carbonate, and only battery-grade lithium carbonate is prepared. Chinese patent document CN102030344A discloses a method for preparing lithium fluoride, wherein lithium fluoride is prepared by using CO2 hydrogenation and hydrofluoric acid reaction, but there are disadvantages such as long hydrogenation reaction time, low CO2 utilization rate, and the product does not meet battery-grade standards.

[0004] Therefore, it is necessary to develop an effective impurity removal and conversion process to utilize industrial-grade lithium carbonate as raw material and ensure the battery-grade quality of the final lithium fluoride product. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate, which can effectively remove impurities in industrial-grade lithium carbonate. The obtained battery-grade lithium fluoride product has high purity and is convenient for industrial production.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] In a first aspect, the present invention provides a method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate, comprising the following steps:

[0008] (1) mixing industrial grade lithium carbonate with an organic acid until the solution no longer reacts;

[0009] (2) adding an auxiliary agent to the solution in step (1), adjusting the pH value with an organic acid and then filtering to obtain a filtrate 1;

[0010] (3) purifying the filtrate 1 obtained in step (2) with a cation exchange resin, and filtering to obtain a filtrate 2;

[0011] (4) adding hydrofluoric acid to the filtrate 2 in step (3) and stirring the reaction until no more precipitate is generated, to obtain a mixture 3;

[0012] (5) The mixture 3 in step (4) is filtered to obtain a filtrate and a filter cake; the obtained filter cake is washed and dried to obtain battery-grade lithium fluoride.

[0013] Preferably, in step (1) and step (2), the organic acid is selected from oxalic acid and formic acid, and the concentration of the organic acid is 10 to 20 wt%.

[0014] Preferably, in step (1), the molar ratio of industrial-grade lithium carbonate to organic acid is 1:1-2.5; and the pH value at the reaction endpoint is 5-6.

[0015] Preferably, in step (2), the auxiliary agent is selected from one of barium hydroxide, barium carbonate, barium oxalate and barium formate, and the amount of the auxiliary agent added is 0.1 to 0.8% of the mass of industrial-grade lithium carbonate.

[0016] Preferably, in step (2), the pH value is 5-6.

[0017] Preferably, in step (3), the brand of the cation exchange resin is D113, and the amount added is 0.5-3% of the mass of the industrial grade lithium carbonate.

[0018] Preferably, in step (4), the concentration of hydrofluoric acid is 8-12 wt %; the stirring reaction temperature is 5-15° C., and the reaction pH is 5-6.

[0019] Preferably, in step (5), the drying temperature is 100-150° C. and the drying time is 3-8 hours.

[0020] Preferably, in step (5), the filtrate is further used to prepare organic acid for reuse.

[0021] In a second aspect, the present invention seeks to protect the battery-grade lithium fluoride product prepared by the above method.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The preparation method provided by the present invention can achieve a total yield of more than 99% by controlling the pH in the solution and optimizing the reaction conditions. The purity of the lithium fluoride product is as high as more than 99.95%. The content of sodium, magnesium, potassium, calcium and iron in industrial-grade lithium carbonate can be effectively removed, and the obtained battery-grade lithium fluoride product has a high purity.

[0024] 2. The preparation method provided by the present invention omits the CO2 hydrogenation step, has high purification efficiency, and is convenient for industrial production.

[0025] 3. In the preparation method provided by the present invention, the filtrate after the reaction can be recovered for further preparation of the organic acid solution and can be reused, which greatly reduces the production cost. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Unless otherwise specified, all commodities or reagents in the present invention were purchased through market channels.

[0028] Example 1

[0029] Take industrial-grade lithium carbonate raw material and set aside; the weight content of industrial-grade lithium carbonate is 99.08%, sodium is 985ppm, magnesium is 115ppm, potassium is 60ppm, calcium is 325ppm, iron is 42ppm, and sulfate is 1752ppm.

[0030] A method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate comprises the following steps:

[0031] (1) Weigh 34.06 g of industrial grade lithium carbonate and add it to a 1 L beaker. Measure 431.74 g of 10% oxalic acid solution and slowly add it to the beaker until no bubbles are generated in the solution. Then add a few drops and stir for about 5 minutes. The pH value of the solution is about 6.

[0032] (2) Weigh 0.03 g of barium hydroxide and add it to a beaker and stir for 5 minutes. Add a few drops of oxalic acid to the solution to adjust the pH of the solution to about 6, and filter to obtain the filtrate;

[0033] (3) The filtrate is then treated with 0.17 g of cation exchange resin (D113) and filtered to obtain a filtrate;

[0034] (4) The filtrate was transferred to a polytetrafluoroethylene beaker, 182.74 g of 10% hydrofluoric acid was prepared, and hydrofluoric acid was added to the solution and stirred until no precipitation was formed (temperature controlled at 10°C), and the pH was measured to be about 5;

[0035] (5) The filtrate was recovered by suction filtration and used to prepare 10% oxalic acid solution. The filter cake was washed three times with deionized water and dried at 100° C. for 3 h to obtain 23.52 g of lithium fluoride.

[0036] After testing: the product yield is 99.27%, the product purity is 99.96%, the impurities sodium is 5ppm, magnesium is 6ppm, potassium is 2ppm, calcium is 3ppm, iron is 5ppm, sulfate is 10ppm, which can meet the battery grade lithium fluoride standard.

[0037] Example 2

[0038] Take industrial-grade lithium carbonate raw material and set aside; the weight content of industrial-grade lithium carbonate is 99.13%, sodium is 687ppm, magnesium is 168ppm, potassium is 58ppm, calcium is 297ppm, iron is 45ppm, and sulfate is 1766ppm.

[0039] A method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate comprises the following steps:

[0040] (1) Weigh 34.19 g of industrial grade lithium carbonate and add it to a 1 L beaker. Measure 289.07 g of 15% oxalic acid solution and slowly add it to the beaker until no bubbles are generated in the solution. Then add a few drops and stir for about 5 minutes. The pH value of the solution is about 6.

[0041] (2) Weigh 0.17 g of barium carbonate and add it to a beaker, stirring for 5 minutes. Add a few drops of oxalic acid to the solution to adjust the pH of the solution to about 6, and filter to obtain the filtrate;

[0042] (3) The filtrate is then treated with 0.51 g of cation exchange resin (D113) and filtered to obtain a filtrate;

[0043] (4) The filtrate was transferred to a polytetrafluoroethylene beaker, 183.53 g of 10% hydrofluoric acid was prepared, and hydrofluoric acid was added to the solution and stirred until no precipitation was formed (temperature controlled at 8°C), and the pH was measured to be about 5;

[0044] (5) The filtrate was recovered by suction filtration and used to further prepare 15% oxalic acid solution. The filter cake was washed three times with deionized water and dried at 120° C. for 6 h to obtain 23.59 g of lithium fluoride.

[0045] After testing: the product yield is 99.13%, the product purity is 99.97%, the impurities are 4ppm sodium, 3ppm magnesium, 4ppm potassium, 5ppm calcium, 6ppm iron, and 13ppm sulfate, which can meet the battery grade lithium fluoride standard.

[0046] Example 3

[0047] Take industrial-grade lithium carbonate raw material and set aside; the weight content of industrial-grade lithium carbonate is 99.16%, sodium is 598ppm, magnesium is 195ppm, potassium is 52ppm, calcium is 288ppm, iron is 49ppm, and sulfate is 1659ppm.

[0048] A method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate comprises the following steps:

[0049] (1) Weigh 34.56 g of industrial grade lithium carbonate and add it to a 1 L beaker. Measure 229.65 g of 20% oxalic acid solution and slowly add it to the beaker until no bubbles are generated in the solution. Then add a few drops and stir for about 5 minutes. The pH value of the solution is about 6.

[0050] (2) Weigh 0.28 g of barium oxalate and add it to a beaker and stir for 5 minutes. Add a few drops of oxalic acid to the solution to adjust the pH of the solution to about 6, and filter to obtain the filtrate;

[0051] (3) The filtrate is then treated with 1.04 g of cation exchange resin (D113) and filtered to obtain a filtrate;

[0052] (4) The filtrate was transferred to a polytetrafluoroethylene beaker, 185.58 g of 10% hydrofluoric acid was prepared, and hydrofluoric acid was added to the solution and stirred until no precipitation was formed (temperature controlled at 10°C), and the pH was measured to be about 5;

[0053] (5) The filtrate was recovered by suction filtration and used to prepare 20% oxalic acid solution. The filter cake was washed three times with deionized water and dried at 140° C. for 7 h to obtain 23.86 g of lithium fluoride.

[0054] After testing: the product yield is 99.17%, the product purity is 99.96%, the impurities sodium is 3ppm, magnesium is 5ppm, potassium is 6ppm, calcium is 2ppm, iron is 4ppm, sulfate is 14ppm, which can meet the battery grade lithium fluoride standard.

[0055] Example 4

[0056] Take industrial-grade lithium carbonate raw material and set aside; the weight content of industrial-grade lithium carbonate is 99.20%, sodium is 498ppm, magnesium is 175ppm, potassium is 66ppm, calcium is 278ppm, iron is 39ppm, and sulfate is 1622ppm.

[0057] A method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate comprises the following steps:

[0058] (1) Weigh 34.38 g of industrial grade lithium carbonate and add it to a 1 L beaker. Measure 304.73 g of 15% oxalic acid solution and slowly add it to the beaker until no bubbles are generated in the solution. Then add a few drops and stir for about 5 minutes. The pH value of the solution is about 6.

[0059] (2) Weigh 0.17 g of barium formate and add it to a beaker and stir for 5 minutes. Add a few drops of oxalic acid to the solution to adjust the pH of the solution to about 6, and filter to obtain the filtrate;

[0060] (3) The filtrate is then treated with 0.34 g of cation exchange resin (D113) and filtered to obtain a filtrate;

[0061] (4) The filtrate was transferred to a polytetrafluoroethylene beaker, 184.68 g of 10% hydrofluoric acid was prepared, and hydrofluoric acid was added to the solution and stirred until no precipitation was formed (temperature controlled at 9°C), and the pH was measured to be about 5;

[0062] (5) The filtrate was recovered by suction filtration and used to further prepare 15% oxalic acid solution. The filter cake was washed three times with deionized water and dried at 150° C. for 4 h to obtain 23.72 g of lithium fluoride.

[0063] After testing: the product yield is 99.06%, the product purity is 99.96%, the impurities sodium is 2ppm, magnesium is 1ppm, potassium is 5ppm, calcium is 4ppm, iron is 7ppm, sulfate is 11ppm, which can meet the battery grade lithium fluoride standard.

[0064] Example 5

[0065] Take industrial-grade lithium carbonate raw material and set aside; the weight content of industrial-grade lithium carbonate is 99.14%, sodium is 652ppm, magnesium is 186ppm, potassium is 69ppm, calcium is 285ppm, iron is 41ppm, and sulfate is 1599ppm.

[0066] A method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate comprises the following steps:

[0067] (1) Weigh 34.26 g of industrial grade lithium carbonate and add it to a 1 L beaker. Measure 505.81 g of 18% formic acid solution and slowly add it to the beaker until no bubbles are generated in the solution. Then add a few drops and stir for about 5 minutes. The pH value of the solution is about 6.

[0068] (2) Weigh 0.03 g of barium hydroxide and add it to a beaker, stirring for 5 minutes. Add a few drops of formic acid to the solution to adjust the pH of the solution to about 6, and filter to obtain the filtrate;

[0069] (3) The filtrate is then treated with 0.69 g of cation exchange resin (D113) and filtered to obtain a filtrate;

[0070] (4) The filtrate was transferred to a polytetrafluoroethylene beaker, 183.93 g of 10% hydrofluoric acid was prepared, and hydrofluoric acid was added to the solution and stirred until no precipitation was formed (temperature controlled at 12°C), and the pH was measured to be about 5;

[0071] (5) The filtrate was recovered by suction filtration and used to further prepare 18% formic acid solution. The filter cake was washed three times with deionized water and dried at 100° C. for 4 h to obtain 23.65 g of lithium fluoride.

[0072] After testing: the product yield is 99.17%, the product purity is 99.96%, the impurities sodium is 3ppm, magnesium is 5ppm, potassium is 7ppm, calcium is 3ppm, iron is 6ppm, sulfate is 9ppm, which can meet the battery grade lithium fluoride standard.

[0073] Example 6

[0074] Take industrial-grade lithium carbonate raw material and set aside; the weight content of industrial-grade lithium carbonate is 99.20%, sodium is 758ppm, magnesium is 149ppm, potassium is 64ppm, calcium is 266ppm, iron is 40ppm, and sulfate is 1584ppm.

[0075] A method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate comprises the following steps:

[0076] (1) Weigh 34.15 g of industrial grade lithium carbonate and add it to a 1 L beaker. Measure 605.39 g of 15% formic acid solution and slowly add it to the beaker until no bubbles are generated in the solution. Then add a few drops and stir for about 5 minutes. The pH value of the solution is about 6.

[0077] (2) Weigh 0.17 g of barium carbonate and add it to a beaker, stirring for 5 minutes. Add a few drops of formic acid to the solution to adjust the pH of the solution to about 6, and filter to obtain the filtrate;

[0078] (3) The filtrate is then treated with 1.03 g of cation exchange resin (D113) and filtered to obtain a filtrate;

[0079] (4) The filtrate was transferred to a polytetrafluoroethylene beaker, 183.45 g of 10% hydrofluoric acid was prepared, and hydrofluoric acid was added to the solution and stirred until no precipitation was formed (temperature controlled at 11°C), and the pH was measured to be about 5;

[0080] (5) The filtrate was recovered by suction filtration and used to further prepare 15% formic acid solution. The filter cake was washed three times with deionized water and dried at 120° C. for 7 h to obtain 23.62 g of lithium fluoride.

[0081] After testing: the product yield is 99.31%, the product purity is 99.97%, the impurities sodium is 2ppm, magnesium is 3ppm, potassium is 5ppm, calcium is 7ppm, iron is 4ppm, sulfate is 11ppm, which can meet the battery grade lithium fluoride standard.

[0082] Example 7

[0083] Take industrial-grade lithium carbonate raw material and set aside; the weight content of industrial-grade lithium carbonate is 99.22%, sodium is 745ppm, magnesium is 119ppm, potassium is 66ppm, calcium is 246ppm, iron is 47ppm, and sulfate is 1533ppm.

[0084] A method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate comprises the following steps:

[0085] (1) Weigh 34.32 g of industrial grade lithium carbonate and add it to a 1 L beaker. Measure 456.39 g of 20% formic acid solution and slowly add it to the beaker until no bubbles are generated in the solution. Then add a few drops and stir for about 5 minutes. The pH value of the solution is about 6.

[0086] (2) Weigh 0.27 g of barium oxalate and add it to a beaker and stir for 5 minutes. Add a few drops of formic acid to the solution to adjust the pH of the solution to about 6, and filter to obtain the filtrate;

[0087] (3) The filtrate is then treated with 0.69 g of cation exchange resin (D113) and filtered to obtain a filtrate;

[0088] (4) The filtrate was transferred to a polytetrafluoroethylene beaker, 184.40 g of 10% hydrofluoric acid was prepared, and hydrofluoric acid was added to the solution and stirred until no precipitation was formed (temperature controlled at 10°C), and the pH was measured to be about 5;

[0089] (5) The filtrate was recovered by suction filtration and used to further prepare a 20% formic acid solution. The filter cake was washed three times with deionized water and dried at 140° C. for 5 h to obtain 23.67 g of lithium fluoride.

[0090] After testing: the product yield is 99.00%, the product purity is 99.96%, the impurities sodium is 4ppm, magnesium is 5ppm, potassium is 2ppm, calcium is 3ppm, iron is 3ppm, sulfate is 15ppm, which can meet the battery grade lithium fluoride standard.

[0091] Example 8

[0092] Take industrial-grade lithium carbonate raw material and set aside; the weight content of industrial-grade lithium carbonate is 99.31%, sodium is 759ppm, magnesium is 188ppm, potassium is 59ppm, calcium is 228ppm, iron is 49ppm, and sulfate is 1745ppm.

[0093] A method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate comprises the following steps:

[0094] (1) Weigh 34.43 g of industrial grade lithium carbonate and add it to a 1 L beaker. Measure 611.03 g of 15% formic acid solution and slowly add it to the beaker until no bubbles are generated in the solution. Then add a few drops and stir for about 5 minutes. The pH value of the solution is about 6.

[0095] (2) Weigh 0.17 g of barium formate and add it to a beaker and stir for 5 minutes. Add a few drops of oxalic acid to the solution to adjust the pH of the solution to about 6, and filter to obtain the filtrate;

[0096] (3) The filtrate is then treated with 1.03 g of cation exchange resin (D113) and filtered to obtain a filtrate;

[0097] (4) The filtrate was transferred to a polytetrafluoroethylene beaker, 185.16 g of 10% hydrofluoric acid was prepared, and hydrofluoric acid was added to the solution and stirred until no precipitation was formed (temperature controlled at 9°C), and the pH was measured to be about 5;

[0098] (5) The filtrate was recovered by suction filtration and used to further prepare 15% formic acid solution. The filter cake was washed three times with deionized water and dried at 150° C. for 8 h to obtain 23.78 g of lithium fluoride.

[0099] After testing: the product yield is 99.06%, the product purity is 99.96%, the impurities sodium is 4ppm, magnesium is 3ppm, potassium is 5ppm, calcium is 3ppm, iron is 4ppm, sulfate is 8ppm, which can meet the battery grade lithium fluoride standard.

[0100] Comparative Example 1

[0101] Take industrial-grade lithium carbonate raw material and set aside; the weight content of industrial-grade lithium carbonate is 99.08%, sodium is 985ppm, magnesium is 115ppm, potassium is 60ppm, calcium is 325ppm, iron is 42ppm, and sulfate is 1752ppm.

[0102] A method for preparing lithium fluoride from industrial-grade lithium carbonate comprises the following steps:

[0103] (1) Weigh 34.06 g of industrial grade lithium carbonate and add it to a 1 L beaker. Measure 431.74 g of 10% oxalic acid solution and slowly add it to the beaker until no bubbles are generated in the solution. Then add a few drops and stir for about 5 minutes. The pH value of the solution is about 6.

[0104] (2) treating the solution with 0.51 g of cation exchange resin (D113) and filtering to obtain a filtrate;

[0105] (3) The filtrate was transferred to a polytetrafluoroethylene beaker, 182.74 g of 10% hydrofluoric acid was prepared, and hydrofluoric acid was added to the solution and stirred until no precipitation was formed (temperature controlled at 10°C), and the pH was measured to be about 5;

[0106] (4) The filtrate was recovered by suction filtration and used to further prepare 10% oxalic acid solution. The filter cake was washed three times with deionized water and dried at 100° C. for 3 h to obtain 23.32 g of lithium fluoride.

[0107] After testing: the product yield was 98.42%, the product purity was 99.81%, the impurities sodium was 7ppm, magnesium was 28ppm, potassium was 6ppm, calcium was 31ppm, iron was 38ppm, and sulfate was 1708ppm, which failed to meet the battery-grade lithium fluoride standard.

[0108] Comparative Example 2

[0109] Take industrial-grade lithium carbonate raw material and set aside; the weight content of industrial-grade lithium carbonate is 99.08%, sodium is 985ppm, magnesium is 115ppm, potassium is 60ppm, calcium is 325ppm, iron is 42ppm, and sulfate is 1752ppm.

[0110] A method for preparing lithium fluoride from industrial-grade lithium carbonate comprises the following steps:

[0111] (1) Weigh 34.06 g of industrial grade lithium carbonate and add it to a 1 L beaker. Measure 431.74 g of 10% oxalic acid solution and slowly add it to the beaker until no bubbles are generated in the solution. Then add a few drops and stir for about 5 minutes. The pH value of the solution is about 6.

[0112] (2) Weigh 0.03 g of barium hydroxide and add it to a beaker and stir for 5 minutes. Add a few drops of oxalic acid to the solution to adjust the pH of the solution to about 6, and filter to obtain the filtrate;

[0113] (3) The filtrate was transferred to a polytetrafluoroethylene beaker, 182.74 g of 10% hydrofluoric acid was prepared, and hydrofluoric acid was added to the solution and stirred until no precipitation was formed (temperature controlled at 10°C), and the pH was measured to be about 5;

[0114] (4) The filtrate was recovered by suction filtration and used to further prepare 10% oxalic acid solution. The filter cake was washed three times with deionized water and dried at 100° C. for 3 h to obtain 23.27 g of lithium fluoride.

[0115] After testing: the product yield was 98.21%, the product purity was 99.91%, the impurities sodium was 5ppm, magnesium was 35ppm, potassium was 5ppm, calcium was 48ppm, iron was 24ppm, and sulfate was 18ppm, which failed to meet the battery-grade lithium fluoride standard.

[0116] Comparative Example 3

[0117] Take industrial-grade lithium carbonate raw material and set aside; the weight content of industrial-grade lithium carbonate is 99.08%, sodium is 985ppm, magnesium is 115ppm, potassium is 60ppm, calcium is 325ppm, iron is 42ppm, and sulfate is 1752ppm.

[0118] A method for preparing lithium fluoride from industrial-grade lithium carbonate comprises the following steps:

[0119] (1) Weigh 34.06 g of industrial grade lithium carbonate and add it to a 1 L beaker. Measure 431.74 g of 10% oxalic acid solution and slowly add it to the beaker until no bubbles are generated in the solution. Then add a few drops and stir for about 5 minutes. The pH value of the solution is about 6.

[0120] (2) The solution was transferred to a polytetrafluoroethylene beaker, 182.74 g of 10% hydrofluoric acid was prepared, and hydrofluoric acid was added to the solution and stirred until no precipitation was formed (temperature controlled at 10°C), and the pH was measured to be about 5;

[0121] (5) The filtrate was recovered by suction filtration and used to further prepare 10% oxalic acid solution. The filter cake was washed three times with deionized water and dried at 100° C. for 3 h to obtain 22.94 g of lithium fluoride.

[0122] After testing: the product yield was 96.82%, the product purity was 99.79%, the impurities were 6ppm sodium, 108ppm magnesium, 7ppm potassium, 311ppm calcium, 39ppm iron, and 1716ppm sulfate, which failed to meet the battery-grade lithium fluoride standard.

[0123] The applicant declares that the present invention illustrates the technical solution of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of individual raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate, characterized in that: The steps include: (1) mixing industrial grade lithium carbonate with an organic acid until the solution no longer reacts; (2) adding an auxiliary agent to the solution in step (1), adjusting the pH value with an organic acid and then filtering to obtain a filtrate 1; (3) purifying the filtrate 1 obtained in step (2) with a cation exchange resin, and filtering to obtain a filtrate 2; (4) adding hydrofluoric acid to the filtrate 2 in step (3) and stirring the reaction until no more precipitate is generated, to obtain a mixture 3; (5) The mixture 3 in step (4) is filtered to obtain a filtrate and a filter cake; the obtained filter cake is washed and dried to obtain battery-grade lithium fluoride.

2. The method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate according to claim 1, characterized in that: In step (1) and step (2), the organic acid is selected from one of oxalic acid and formic acid, and the concentration of the organic acid is 10 to 20 wt%.

3. The method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate according to claim 1, characterized in that: In step (1), the molar ratio of industrial-grade lithium carbonate to organic acid is 1:1-2.5; and the pH value at the reaction end point is 5-6.

4. The method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate according to claim 1, characterized in that: In step (2), the auxiliary agent is selected from one of barium hydroxide, barium carbonate, barium oxalate and barium formate, and the amount of the auxiliary agent added is 0.1 to 0.8% of the mass of industrial-grade lithium carbonate.

5. The method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate according to claim 1, characterized in that: In step (2), the pH value is 5-6.

6. The method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate according to claim 1, characterized in that: In step (3), the brand of the cation exchange resin is D113, and the amount added is 0.5-3% of the mass of the industrial grade lithium carbonate.

7. The method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate according to claim 1, characterized in that: In step (4), the concentration of hydrofluoric acid is 8-12 wt %; the stirring reaction temperature is 5-15° C., and the reaction pH value is 5-6.

8. The method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate according to claim 1, characterized in that: In step (5), the drying temperature is 100-150° C. and the drying time is 3-8 hours.

9. The method for preparing battery-grade lithium fluoride from industrial-grade lithium carbonate according to claim 1, characterized in that: In step (5), the filtrate is further used to prepare organic acid for reuse.

10. Battery-grade lithium fluoride prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of lithium fluoride

    CN102030344A

  • Battery-grade lithium carbonate preparation method based on phase transformation

    CN105502442A

  • Method for preparing battery-grade lithium carbonate by purifying industrial-grade lithium carbonate

    CN110817910A

  • Preparation method of lithium carbonate

    CN117247032A

  • Process and system for preparing battery-grade lithium fluoride from industrial lithium carbonate

    CN117401698A